Storage of mungbean seed (Vigna radiata (L) Wilczek) inoculated with four species of Aspergilli - Wan Nik, Wan Zainun; Mamat, Hasbullah (1982)
Four species of AJpergilli namely Aspergillus flavus, A. niger, A. fumigatus and A. parasiticus were used in the study. Mungbean seeds were inoculated with the the above fungi; mould invasion and percent germination up to 18 weeks of storage at 30%, 50% and 95% RH were evaluated. The infection due to A. flavus, A. fumigatus and A. parasiticus was greater than 80% after 18 weeks of storage at 95% relative himidity (RH). Maximum infection of 90% by A. niger was obtained after 9 weeks of storage at 95% RH but thereafter, the percentage infection decreased. At 30% and 50% RH, infection by A. fumigatus was lowest while that of A. flavus was highest after 18 weeks of storage. Seeds stored at 30% and 50% RH did not show any decline in germination even after the 18th week of storage. However, seed stored at 95% RH showed a decline in germination after the 12th week of storage.